Effect of modified atmosphere package on apricot fruit storability - Ezzat, A. (International Journal of Horticultural Science, 2018)
The aim of this work was to study the effect of modified atmosphere package (MAP) on apricot storability. Apricots (Prunus armeniaca L.) cultivar Jumbo cot were harvested at commercial ripening stage. The fruits were treated with different storage treatments as following: i) control storage for 13 days at 1 °C, ii) stored fruit at 1 °C for 10 days then 3 days at shelf at 25 °C, iii) fruit stored in MAP at 1 °C for 13 days and iv) fruit stored in MAP at 1 °C for 10 days then 3 days at shelf at 25 °C. Data showed the positive effect of MAP in keeping the apricot fruit for long time with better quality than the control fruit. MAP showed positive effect by recording the lowest fruit weight loss, the highest firmness and lowest chilling injury and fruit decay.